IN VITRO IN VIVO STUDIES ON FLOATING MICROSPHERES FOR GASTRORETENTIVE DRUG DELIVERY SYSTEM: A REVIEW - KRISHNA; KUMAR, ABHISHEK; SRIVASTAVA, RAJAT (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The purpose of writing this review on gastroretentive drug delivery systems (GRDDS) was to compile the recent literature with a special focus on various gastroretentive approaches that have recently become leading methodologies in the field of site-specific orally administered controlled release drug delivery. One of the complex processes in the human body is gastric emptying, as it is highly variable, which makes the in vivo performance of the drug delivery systems uncertain. GRDDS has gained immense popularity in the field of oral drug delivery recently. It is a widely employed approach to retain the dosage form in the stomach for an extended period of time and release the drug slowly that can address many challenges associated with the conventional oral delivery system. Conventional drug delivery systems may not overcome the issues imposed by the gastrointestinal tract (GIT) such as incomplete release of drugs, decrease in dose effectiveness, and frequent dose requirement. To overcome this variability, a controlled drug delivery system with a prolonged gastric residence time of >12 h in the stomach can be of great practical importance for drugs with an absorption window in the upper small intestine. GRDFs enable prolonged and continuous release of the drug to the upper part of the GIT and thus significantly extend the duration of drug release and improve the bioavailability of drugs that have a narrow therapeutic window; by this way, they prolong dosing interval and increase compliance.